1935
DOI: 10.1021/ed012p49.2
|View full text |Cite
|
Sign up to set email alerts
|

Units in Chemistry (Howard, Russell S.)

Abstract: This is a workbook providing explanations of-d drill inthe fundamentals of arithmetic, algebra, geometry, and trigonometry, with the major emphasis on algebra. It is the joint product of a professor of mathematics, a professor of physics, and a professor of educational psychology, each contributing his own point of view and his own experience. Its content is based upon: (1) first-hand experience with college freshmen, (2) actual analysis of the requirements of first courses in college mathematics, physics, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Grain boundaries are the most important diffusion paths for polycrystalline films. 11 Whipple 12 and Suzuoka 13 used Fourier and Laplace transforms to solve the problem of coupled lattice and grain boundary diffusion treated as a continuum. Although the lattice and grain boundary diffusion coefficients of Cu in tantalum nitride thin films are essential for the Whipple model, 12 they have never been measured directly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Grain boundaries are the most important diffusion paths for polycrystalline films. 11 Whipple 12 and Suzuoka 13 used Fourier and Laplace transforms to solve the problem of coupled lattice and grain boundary diffusion treated as a continuum. Although the lattice and grain boundary diffusion coefficients of Cu in tantalum nitride thin films are essential for the Whipple model, 12 they have never been measured directly.…”
mentioning
confidence: 99%
“…Auger electron spectroscopy (AES) incorporating ion sputteringetching has been successfully used for measuring thin film diffusion by determining the profiles of diffusion species. 9,11,16,17 A detailed study on some problems intrinsic to the Auger profiling technique for diffusion measurements has been done by Wildman et al 11 They showed that AES is a good technique for diffusion measurements with some cautions. This work focuses mainly on measuring the temperature and composition dependencies of Cu diffusion in tantalum nitride polycrystalline films and to propose the Whipple model 12,13 as a useful model for analyzing and simulating the diffusion process.…”
mentioning
confidence: 99%